Comprehensive Survey and Heritage Value Evaluation of Weiyuan Settlement Remains on China’s Jianghan Plain - Liu, Xiaohu; Lei, Dian; Tan, Gangyi; Wang, Zheyu; Zhao, Bing; Chen, Guojun; Peng, Xing; Oliveira, Luana; Rena, Natacha (International Planning History Society Proceedings, 2024)
The Jianghan Plain in the middle reaches of the Yangtze River was covered mainly by the ancient Yunmeng Marsh for an extended period. Many primitive residential forms related to water, such as Ganlan (elevated sheds), Haopai (wormwood rafts), and Weiyuan (circular embankments), emerged as early humans developed this vast region. They used Ganlan to settle at the lake edges, Haopai to explore deeper waters, and eventually mastered Weiyuan construction techniques. They discovered that building Weiyuan embankments could permanently secure parts of the swamp, leading to the creation of early Weiyuan settlements. Over millennia, Weiyuan evolved from water conservancy structures in prehistoric settlements into complex residential units during the Ming and Qing dynasties. These units formed water conservancy commonwealths, developing into micro-hydraulic societies. Recent urbanisation has severely damaged Weiyuan, posing a risk of complete disappearance, necessitating urgent surveys and protection. The vast Jianghan Plain makes it challenging to discover Weiyuan remains. This study employed machine vision to identify 210 villages (towns) with potential Weiyuan remains. After comparing them with historical maps, 136 Weiyuan settlement samples were selected and classified into 4 grades (A, B, C, and D) based on their integrity. Field investigations identified six towns and seven villages with well-conserved Weiyuan remains. Specific measures for protecting and optimising contemporary Jianghan Plain villages and towns centred on “Yuan” are proposed.